Job Satisfaction to Enhance Leadership Style of The Principal - Sutji Harijanto (STKIP Singkawang, 2018)
This study aims to explore job satisfaction enhances the leadership style of the principal. This study uses a survey which obtained 60 samples from an affordable population of 146 senior high school headmaster by taking them through simple random sampling. The result shows that teacher’s job satisfactions strengthened the higher score of the leadership style of the principal. Finally, a teacher’s job satisfaction for teaching practices were examined at one point in time. The quality of leadership style of the principal will increase.